Bone cement filling combined with lumbo‐iliac screw internal fixation in the treatment of benign sacroiliac joint tumours. Issue 1 (22nd December 2021) - Pu, Feifei; Liu, Jianxiang; Zhang, Zhicai; Wang, Baichuan; Shao, Zengwu
Abstract: Background: To investigate the method of reconstruction of the sacroiliac joint in patients who underwent benign tumour curettage and analyse the effect of internal fixation with lumbo‐iliac screws and connecting rod insertion after filling the defect with bone cement. Methods: Twenty‐four patients with benign sacroiliac joint tumours underwent curettage and filling of the defect with bone cement, followed by lumbo‐iliac screw and connecting rod insertion. The visual analogue scale (VAS) was used to assess pain, and the Musculoskeletal Tumour Society (MSTS) score was used to assess hip function. Results: All patients were followed‐up for 24–96 months (average, 42.2 months). The postoperative VAS score was significantly lower than the preoperative score ( p < 0.05), while the postoperative MSTS score was significantly higher than the preoperative score ( p < 0.05). One patient had delayed healing of the surgical incision; no complications occurred in the remaining patients. Conclusion: For benign sacroiliac joint tumours, the combination of filling of defects with bone cement and internal lumbo‐iliac fixation can relieve pain quickly, and achieve good limb function. Abstract : Sacroiliac joint tumours are relatively rare, and there is no uniform management for surgical resection and reconstruction of tumours at this location. Bone cement filled bone defect, combined with lumbar and iliac pin fixation, can achieve stable reconstruction.